Application of the Kvaal method for age estimation using digital panoramic radiography of Chinese individuals. (August 2019) - Li, Mu-jia; Chu, Guang; Han, Meng-qi; Chen, Teng; Zhou, Hong; Guo, Yu-cheng
Highlights: The most significant correlation between actual age and ratios was for ratio B. Six ratios of mandibular canine teeth showed a significant correlation with age. A Chinese-specific equation could ameliorate age prediction accuracy. The standard deviations for the Chinese-specific equation remained large. Abstract: The Kvaal method as a non-invasive method for age estimation based on the changes of pulpal size caused by secondary dentin deposition has been applied to different ethnics. However, its results are often conflicting and its accuracy is relatively poor. This study aimed to verify the applicability of the Kvaal method to estimate the ages of the Chinese population using digital panoramic radiographs and to formulate specific regression equations for use in Chinese subjects. A sample of 360 digital panoramic radiographs from northern Chinese population were selected, from which the pulpal size and width of six tooth types (maxillary central incisor, lateral incisor, second premolar, mandibular lateral incisor, canine, and first premolar) were measured using Kvaal's method. Then, inter- and intra-observer reliabilities were calculated to evaluate the reproducibility of those measurements. The correlation between chronological age and measurements was also examined and the Chinese-specific equations for age estimation were conducted. After comparing the accuracy of the Chinese-specific equation with the original Kvaal equation, the age of the Chinese population was clearly overestimated by Kvaal's equation, and a Chinese-specific equation could ameliorate age prediction accuracy. In addition, the residuals of the Chinese-specific equation were significantly lower than that of the original Kvaal's method. Thus, we concluded that the original Kvaal equation cannot accurately estimate age in the Chinese population. Although accuracy improved using the Chinese-specific equation that was based on Kvaal's methodology, the standard deviation remained large. In view of the lack of accurate age estimation methods for adults, we propose finding more correlated variables or combining other age estimation methods to increase the accuracy for adult age estimation.